USA-DSL process : a usability evaluation process for domain-specific languages - Rodrigues, Ildevana Poltronieri (2021)
Currently, there are different Domain-Specific Languages (DSL) that are created to solve problems in a particular domain and are not intended to solve problems outside their scope. According to Fowler, a DSL is a computational language focused on a particular domain, however, its expressiveness is Limited to that specific domain. These languages are classified according to their form of implementation and can be internal, external, and graphic. Thus, from the different applications and classifications of DSLs, a concern has been pertinent: the usability evaluation the developed languages. As for the evaluation of these languages, several experimental studies can be found subjectively evaluating usability, but few have appropriated the specific techniques of Human-Computer Interaction (IHC). Therefore, this thesis seeks to identify the state of the art regarding the usability evaluation process for DSL. Based on a framework of usability evaluation for DSL and the studies found in the literature, we developed a usability evaluation process for DSLs, which is user-centric